2022
DOI: 10.3390/plants11081018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Thermal Plasma Treatment on Plant Physiological and Biochemical Processes

Abstract: Plasma, also called the fourth state of matter, is partially or fully ionized gas [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Plasma treatment affects the wettability of the coated seed. Investigations of plasma-induced changes in plant physiology and biochemistry are likely to reveal new facts of fundamental and applied interest (Mildaziene and Sera, 2022). Our findings indicate remarkable responses of wheat seeds and seedlings to plasma.…”
Section: Discussionmentioning
confidence: 68%
“…Plasma treatment affects the wettability of the coated seed. Investigations of plasma-induced changes in plant physiology and biochemistry are likely to reveal new facts of fundamental and applied interest (Mildaziene and Sera, 2022). Our findings indicate remarkable responses of wheat seeds and seedlings to plasma.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the PAW creates a higher amount of hydrogen peroxide (H 2 O 2 ) and nitric oxides (NO), longer half-life molecules which may alter the phytohormone balance in the seeds and promote germination [ 49 ]. Recently, Mildaziene and Sera [ 50 ] and Priatama et al [ 51 ] observed that the accumulation of ROS and RNS triggers changes in proteomic, metabolomic and transcriptomic levels and also affects phytohormone levels. The cavitation bubbles which occur during the HVED treatment create UV emission which could also be meritorious for germination dormancy disruption [ 9 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are a large number of ways to obtain low-temperature plasma [1]. Such plasma is widely used in natural sciences, such as chemistry, physics, biology, medicine and agriculture [2][3][4]. It is known that low-temperature plasma interacts with various molecules, including biological ones [5].…”
Section: Introductionmentioning
confidence: 99%